The effect of using entry-level keyboards in improving user-adaptability to new keyboards: Case of the Central-Bantu keyboards - Thokozani Chimkono; Amelia Taylor; Eunice Mphako-Banda; Pascal Kishindo (Telematics and Informatics Reports, 2023)
Current trends in keyboard design show that QWERTY-similarity is a key factor for high user-adaptability keyboard design. This design approach has the challenge that the higher the similarity the lower the text-entry rate for the optimized keyboard. This article reports on the findings of an empirical study which we conducted on QWERTY-users to measure the effect of using an entry-level keyboard in improving user-ability to adapt to a new keyboard. The study used two Central-Bantu physical keyboards (entry-level: with high QWERTY-similarity, and advanced-level: with low similarity) which we had designed in an earlier study. The empirical study obtained learning-curves of the Advanced-level keyboard, of a 12-participant group which was first introduced to an entry-level keyboard, against a control-group of similar size, in a longitudinal study design. A two-sample t-test on the empirical results showed that the entry-level approach caused a marginally significant text-entry-rate improvement of 9.4% with p < .09. A two-sample U-test on word-error rates indicated a non-significant improvement of 8.4%. Our study has shown that the use of entry keyboards is an effective strategy in improving keyboard user-adaptability.